Contributions of volunteering university’s student to national economy - Normah, Awang Noh; Muhamad Fazil, Ahmad; Kamal, M.Y. (AESS Publication, 2017)
Volunteerism refers to voluntary activities that are not intended to obtain material rewards. It is also activities that benefit volunteers as well as to assist societies either formally or informally and also involve individual or collective action. Volunteerism is a global issue that is increasingly gaining attention due to its importance to individuals, communities, and countries. The contribution of undergraduate's student volunteering is not only seen through self-development and society but also on the economic development of the nation. However, people often overlook the issue and link productivity and economic generation to the public and private sectors. This situation caused the voluntary value being economically vague and less attention in most countries especially in developing countries. In this regard, the study was conducted to see how the involvement of undergraduate's students in volunteerism impacts the economic value of a country. In order to see clearly the contribution of volunteering from the economic point of view, the value of engagement time in volunteerism is converted into the number of paid employees and the amount of money.